Mice Lacking Endoglin in Macrophages Show an Impaired Immune Response. - Luisa Ojeda-Fernández; Lucía Recio-Poveda; Mikel Aristorena; Pedro Lastres; Francisco J Blanco; Francisco Sanz-Rodríguez; Eunate Gallardo-Vara; Mateo de las Casas-Engel; Ángel Corbí; Helen M Arthur; Carmelo Bernabeu; Luisa M Botella (PLoS Genetics)
Endoglin is an auxiliary receptor for members of the TGF-β superfamily and plays an important role in the homeostasis of the vessel wall. Mutations in endoglin gene (ENG) or in the closely related TGF-β receptor type I ACVRL1/ALK1 are responsible for a rare dominant vascular dysplasia, the Hereditary Hemorrhagic Telangiectasia (HHT), or Rendu-Osler-Weber syndrome. Endoglin is also expressed in human macrophages, but its role in macrophage function remains unknown. In this work, we show that endoglin expression is triggered during the monocyte-macrophage differentiation process, both in vitro and during the in vivo differentiation of blood monocytes recruited to foci of inflammation in wild-type C57BL/6 mice. To analyze the role of endoglin in macrophages in vivo, an endoglin myeloid lineage specific knock-out mouse line (Eng(fl/fl)LysMCre) was generated. These mice show a predisposition to develop spontaneous infections by opportunistic bacteria. Eng(fl/fl)LysMCre mice also display increased survival following LPS-induced peritonitis, suggesting a delayed immune response. Phagocytic activity is impaired in peritoneal macrophages, altering one of the main functions of macrophages which contributes to the initiation of the immune response. We also observed altered expression of TGF-β1 target genes in endoglin deficient peritoneal macrophages. Overall, the altered immune activity of endoglin deficient macrophages could help to explain the higher rate of infectious diseases seen in HHT1 patients.